ANALYSIS OF WAYS TO INCREASE THE EFFICIENCY OF THE IMPLEMENTATION OF HALAL STANDARDS IN THE REPUBLIC OF UZBEKISTAN - Sultan’s Dildoaxon; Nabiev Abbek (Galaxy International Interdisciplinary Research Journal, 2023)
This article analyzes ways to improve the efficiency of implementing the Halal standard. Halal catering areas, restaurants, hotels, canteens, canteens and buffets, self-service outlets, ready-to-eat supermarkets, bakeries and confectioneries, the raw materials used in such areas, preparation, storage and determine consumption requirements.